Fluorescence-estimated oil concentration (Foil) in the Deepwater Horizon subsea oil plume. (July 2022) - Conmy, Robyn N.; Hall, Alexander; Sundaravadivelu, Devi; Schaeffer, Blake A.; Murray, Andrew R.
Abstract: Tracking the subsea oil plume during the 2010 Deepwater Horizon Oil Spill (DWH) was conducted using in situ fluorescence via vertical profilers ( n  = 1157) and discrete sample chemical analyses ( n  = 7665). During monitoring efforts, discrete samples provided a coarse picture of the oil plume footprint, but the majority of the samples were below standard analytical detection limits for petroleum hydrocarbons. In situ fluorescence data improved the spatial and temporal resolution of the subsea oil plume characterization. Here we synthesized millions of continuous fluorescence data points from hundreds of contemporaneously discrete samples collected to demonstrate how fluorescence could serve as a proxy for Benzene-Toluene-Ethylbenzene-Xylene (BTEX) concentration. Data mined from Gulf Science Data repository were well correlated, and geographically and temporally aligned to provide direct comparisons. Described here are the methods used to calibrate the fluorescence data and to spatially approximate the three-dimensional geographic extent of the oil plume. Graphical abstract: Unlabelled Image Highlights: Submersible fluorescence can be a proxy for petroleum hydrocarbon concentrations. Fluorescence-estimated oil concentrations expand measurements for plume tracking. Modeled regressions of sensors and petroleum bottle samples are well correlated. Spill response operations benefit from improved 3D resolution of plume surveillance.